HUBUNGAN PENGETAHUAN PERAWAT DENGAN PEMBERIAN OBAT HIGH ALERT PRINSIP 7 BENAR DI RUANG RAWAT INAP MURNI TEGUH MEMORIAL HOSPITAL MEDAN - Mega Intan Hartati Tafonao; Seriga Banjarnahor (Indonesian Trust Nursing Journal, 2026)
Medication administration is an essential nursing responsibility that directly affects patient safety. Errors in administering high-alert medications can cause serious or even fatal consequences. Therefore, implementing the “Seven Rights” principle in medication administration is crucial to prevent medication errors. This study aimed to determine the relationship between nurses’ knowledge and compliance in administering high-alert medications based on the Seven Rights principle at the inpatient wards of Murni Teguh Memorial Hospital Medan. This research employed a quantitative method with a cross-sectional design. The sample is 69 nurses and research instrument was a questionnaire. The Spearman's rho correlation test yielded a correlation coefficient of 0.589 with a significance level of 0.000 (p <0.05). This indicates a significant relationship between nurses' knowledge and compliance. The correlation coefficient of 0.589 is within the range of 0.51–0.75, indicating a strong relationship. In conclusion, adherence to the seven rights principle correlates with nurses' understanding of how to administer high-risk medications. It is recommended that nurses improve training and supervision from nursing management.